ANALISIS PENGARUH KESESUAIAN KOMPENSASI, KEPATUHAN SISTEM PENGENDALIAN DAN KOMITMEN ORGANISASI TERHADAP KECURANGAN (FRAUD) PADA PEGAWAI DI INSTANSI PEMERINTAH KOTA SALATIGA - Fudji Sri Mar’ati; Erna Sudarmawanti (Faculty of Economic and Business Universitas STIKUBANK, 2021)
One of the pillars in the Sustainable Development Goals (SDGs) is the 16 pillars covering legal development and governance. Governance in government is one part of this goal, because there are still relatively many forms of fraud in government. The purpose of this study was to analyze the effect of compensation suitability, control system compliance and organizational commitment to fraud. This study took a sample of accounting officers and goods or asset managers throughout the OPD in the City of Salatiga. The analysis tool uses multiple linear regression analysis. This study showsthat the suitability of compensation and control system compliance has no effect on fraud, while organizational commitment has an influence on fraud.Keywords: suitability of compensation, control system compliance, organizational commitment and fraud